Implementasi Sitomas (Sistem Tong Sampah Minim Asap) Sebagai Upaya Pengendalian Polusi Asap dan Limbah Sampah di Desa Citepok, Kecamatan Paseh, Kabupaten Sumedang: Pengabdian - Tia Pebriyant; Nabila Zilfa Amanda; Marsanda Lasmita; Hasna Salsabila; Rahma Shafa Ferisssa; Irene Rilla Pinelda; Aji Nurvijal; Encep Rama Pramudita; Nabila Julianti; Dinda Lovia Nasution; Hernawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Household waste management in Citepok Village, Paseh District, Sumedang Regency, faces significant challenges, particularly due to the absence of a Temporary Disposal Site (TPS), leading residents to open burning practices. This study aimed to describe the implementation of the Low-Smoke Waste Bin System (SiTomas), evaluate its effectiveness in reducing smoke emissions, and assess community acceptance of this innovation. A descriptive qualitative approach was employed with research subjects including residents as users, village officials as supervisors, and us as students from Universitas Muhammadiyah Bandung facilitating the SiTomas implementation. Research procedures involved preparation, socialization, implementation, assistance, and evaluation. Results showed that after the SiTomas use, smoke intensity significantly decreased, community participation increased, and collective awareness of waste management improved compared to pre-implementation conditions. The implementation of this system enhanced local air quality, reinforced social responsibility culture, and provided a replicable model for sustainable waste management in other villages.